BIAYA TRANSAKSI DAN ANALISIS KEUNTUNGAN PETANI PADA SISTEM RESI GUDANG KOPI ARABIKA GAYO DI KABUPATEN ACEH TENGAH - Keumala Fadhiela; Dwi Rachmina; Ratna Winandi (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2018)
The purpose of this study was to analyze the structure of transaction cost and analyze farmers profit on Arabica Gayo Coffee Warehouse Receipt System (WRS) in Central Aceh District. Transaction Costs Analysis (TCA) was used to analize transaction cost structure at selling delay activity and financing activity on WRS. While the ratio of transaction costs to farmers' profit was used to determine the level of effectiveness of WRS. The research was conducted at PT. Ketiara Warehouse, West Aceh district, Aceh. The selected samples were all 4o farmers of Arabica Gayo WRS in Central Aceh Regency. The highest transction cost was on delay selling activity (64,07%) than transaction cost on warehouse receipt financing activity (35,93%). Implementation of the warehouse receipt system in PT. Ketiara provided more benefits to the participants because average percentage ratio between the cost of the transaction with the benefit of <10 percent. Transaction costs and effectiveness of WRS need more attention and focus on the improvement of these two things to maximize the implementation and sustainability of Gayo Arabica Coffee WRS in Central Aceh District.